Pengaruh Corporate Social Responsibility Terhadap Citra Universitas Singaperbangsa Karawang - Evan Fadillah Setiaki; Ajat Sudrajat (STIE AMKOP, 2023)
This study aims to determine, analyze, and explain the influence of Corporate Social Responsibility on the image of Singaperbangsa Karawang University. The research was conducted using quantitative research methods and using descriptive and verification methods. The sample used in this study were 42 respondents from the UNSIKA community population. The analytical technique used is the scale range analysis technique and path analysis with the help of the Method of Successive Interval (MSI), Microsoft Excel 2010 and SPSS version 26 software. Kata Kunci: Corporate Social Responsbility, Citra